Comprehensive analysis of the multi-rings mitochondrial genome of Populus tomentosa - Kai Gao; Ting Guo; Xinmin An (BMC Genomics)
Abstract Background Populus tomentosa, known as Chinese white poplar, is indigenous and distributed across large areas of China, where it plays multiple important roles in forestry, agriculture, conservation, and urban horticulture. However, limited accessibility to the mitochondrial (mt) genome of P. tomentosa impedes phylogenetic and population genetic analyses and restricts functional gene research in Salicaceae family. Results Single-molecule real-time (SMRT) sequencing technology was used to sequence, assemble, and annotate the mt genome of P. tomentosa. This genome has a complex structure composed of four circular molecules ranging from 153,004 to 330,873 base pairs (bp). Each of these four circular molecules contains unique gene sequences that constitute the mt genome of P. tomentosa. The mt genome comprises 69 functional genes, including 38 protein-coding genes (PCGs), 26 tRNA genes, and 5 rRNA genes. After removing duplications, 19 different tRNA coding genes remain, though only 10 amino acids can be recognized. The noncoding region constitutes 93.38% of the mt genome, comprising a large number of repetitive sequences, gene spacer regions, and insertion from chloroplast sequences. Specifically, 40 chloroplast-derived sequences, with a total length of 24,381 bp, were identified in P. tomentosa. Conclusions In the current study, the results provide mitochondrial genomic evidence for the maternal origin of P. tomentosa and enhance understanding of the gene dialog between organelle genomes, contributing to the conservation and utilization of the genetic resources of P. tomentosa.